A Survey of Treatment Trends for Acute Quadriceps Tendon Ruptures Among North American Surgeons. Issue 3 (25th March 2022) - Matthies, Norah-Faye; Paul, Ryan A.; Dwyer, Tim; Chahal, Jaskarndip; Whelan, Daniel
Background: To date, little clinical evidence exists to support a specific surgical technique or postoperative rehabilitation protocol for quadriceps tendon ruptures. With a lack of evidence-based superiority, assessment of clinical practices and surgeon preferences is pertinent. Purpose: To describe the current surgical technique and rehabilitation preferences among members of the Canadian Orthopaedic Association and American Orthopaedic Society for Sports Medicine pertaining to acute quadriceps tendon rupture. Study Design: Cross-sectional study. Methods: Orthopaedic staff members of the Canadian Orthopaedic Association and American Orthopaedic Society for Sports Medicine were invited to complete an internet-based survey composed of 26 questions assessing current trends in the management and rehabilitation of acute quadriceps tendon rupture. Survey questions were developed after a thorough review of current literature. Survey responses were analyzed and reported using descriptive statistics (absolute values, frequencies, and percentages) where appropriate. Statistical comparisons and contrasts between Canadian and American surgeons were made using chi-square analyses and Student t tests. Results: A total of 264 surgeons participated in the survey (136 Canadians; 128 Americans). Canadian surgeons were more likely to obtain a preoperative ultrasound as compared with Americans (43.0% vs 6.7%; P < .00001), while American respondents were more likely to obtain magnetic resonance imaging scans (65.8% vs 10.2%; P < .00001). The transosseous drill hole technique was the most commonly utilized (70.2%); the suture anchor technique was used 20.6% of the time. Canadian respondents trended toward a higher use of transosseous tunnels; however, this was not statistically significant (75.8% vs 64.2%; P = .068). American respondents were more likely to utilize suture anchors (27.5% vs 14.1%; P = .0096). Most respondents advanced range of motion goals stepwise in 2-week intervals of 30° (Canadians, 54.0% vs Americans, 58.5%; P = .3091); timing of range of motion initiation varied. Conclusion: Among North American surgeons who responded to this study, the transosseous technique was the most commonly used, and range of motion was generally advanced in a 2-week stepwise fashion. We found several differences in practice between Canadian and American respondents, including the type of preoperative imaging and the frequency of using the suture anchor technique.